A toponímia africana em Minas Gerais - Emanoela Cristina Lima (2012)
In this assignment, aiming to contribute to the linguistic -cultural investigations concerning to the formation of the portuguese language in Brazil, we have accomplished the study of the places names which were probably of african origin that compose part of the toponymic reality of the territory of Minas Gerais. As it is known, the significant presence o f black people, initiated in the 18th and 19th centuries, period in which began the process of population of the territory of Minas Gerais, has left residues in several aspects of local culture and, consequently, in the lexicon toponymic of Minas Gerais. Being aware of this fact and also knowing that the toponyms testify the history of language, since the linguistic and cultural contacts between peoples are often recorded and kept by these linguistic signs, we proposed to study them, pointing to their occurrences, describing and investigating them, according to Dauzat (1926) and Dick (1990a, 1990b and 2004) theoretical and methodological base. The corpus of this research is originating from the database of the ATEMIG Project (FALE/ UFMG), in which are recorded all toponyms of Minas Gerais that are present in the IBGE topographic maps. For linguistic analysis of lexical databases, we used general, etymological and morphological dictionaries, and various vocabularies that bring together words of the possible african origin. The analysis of lexical databases demonstrated that the words of bantu origin were predominant in the toponymy of Minas Gerais; of 1480 africanisms that composes our corpus, 898 are of bantu origin. The hybridisms were also quite recurring, especially those ones formed by bantu + portuguese. The analysis of toponymic taxonomies showed that, among the toponyms of probable african origin of Minas Gerais, there was a greater occurrence of taxonomies of antropocultural kind. The most recurrent toponymic motivation in this state was represented by the names related to social activities of man, the sociotoponyms. The quantification of africanisms of Minas Gerais showed a low percentage margin of toponyms of african base in all regions of Minas Gerais. The Oeste de Minas presented the most frequence of african base toponyms and the Jequitinhonha Region presented the less of them.